Co-chair report: African Elephant Specialist Group - Holly Dublin (Pachyderm)
Refers to the recent AfESG meeting in Mombasa noting the plenary session and working groups focused on two aspects: the interaction between people and elephants, and the continuing killing of elephant associated with the illegal ivory trade. basic guidelines for collection of field-based information on illegal activites were drawn up. The growing stockpiles of ivory within range states, the decline of law enforcement budgets across the continent were noted. Participants reviewed data relevant for the forthcoming AED.